Studying the Connection Between Partical Size and Lattice Distortions Through X - Ray Diffraction Line Profile Analysis for CaO Powder - Harbi, K .H (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
The integral breadth method has been utilized to analyse line proIiles broadening and lattice strain of CaO at different temperatures The effect of tcmperattre on crystallite size and strain has also been investigated . The crystall i tes are found to be highly anisotropic even at high temperatures